2021
DOI: 10.1002/adhm.202100119
|View full text |Cite
|
Sign up to set email alerts
|

Electrode Materials for Chronic Electrical Microstimulation

Abstract: Electrical microstimulation has enabled partial restoration of vision, hearing, movement, somatosensation, as well as improving organ functions by electrically modulating neural activities. However, chronic microstimulation is faced with numerous challenges. The implantation of an electrode array into the neural tissue triggers an inflammatory response, which can be exacerbated by the delivery of electrical currents. Meanwhile, prolonged stimulation may lead to electrode material degradation., which can be acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 199 publications
(293 reference statements)
0
44
0
Order By: Relevance
“…This challenge is more pronounced in stimulating implants that require a certain voltage across their electrode pair. With the limited area, stimulating electrodes will have to utilize novel rough materials with large charge-injection capacity and small impedance (Pranti et al 2018 ; Khalifa et al 2015 ; Zheng et al 2021 ).…”
Section: Challenges and Progressmentioning
confidence: 99%
“…This challenge is more pronounced in stimulating implants that require a certain voltage across their electrode pair. With the limited area, stimulating electrodes will have to utilize novel rough materials with large charge-injection capacity and small impedance (Pranti et al 2018 ; Khalifa et al 2015 ; Zheng et al 2021 ).…”
Section: Challenges and Progressmentioning
confidence: 99%
“…[ 163 ] Several electrode characteristics, including size, probe shape, cross‐sectional area, and surface roughness, have been adapted to create better control over the charge injection limit to reduce irreversible reactions. [ 165 ]…”
Section: Commonly Used Electronic Materialsmentioning
confidence: 99%
“…These irreversible reactions are generally undesirable, as they may damage interfaced cells and tissues, induce inflammation, and impair electrode function. [ 165 ] Thus, applied voltages are typically maintained within the so‐called “water window” (≈‐0.6 V to 0.8 V), which has been established as a safe range for use in tissues to avoid hydrolysis and irreversible electrochemical reactions. [ 164,166 ]…”
Section: Biomaterials Design Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Because of the ability to tune electrical activity, a high requirement on the safe charge injection limit (Q inj , i.e., the electrochemical capacitance) of ES is also required. [18] In the authors' previous work, [19] we showed that the electrically stimulated repair of the un-regenerable optic nerve could be realized through improvements to the electroactivity of the nanoelectrode used. This was achieved by using a nanofiber electrode made from polypyrrole-modified graphene.…”
Section: Introductionmentioning
confidence: 99%